Creating powerful brands - De Chernatony, Leslie; McDonald, Malcolm; Wallace, Elaine (Oxford ; Burlington, MA : Butterworth-Heinemann, 2003)
This has long been the one book that students can rely on to get them thinking critically and strategically about branding. This new fourth edition is no exception. The definitive introductory textbook for this crucial topic, it is highly illustrated and comes packed with over 50 brand-new, real examples of influential marketing campaigns. Bullets: . Summarises the latest thinking and best practice in the domain of branding . All new real marketing campaigns show how branding theories are implemented in practice . Brought right up to date with a clear European and UK focus.
Previous ed.: Oxford: Elsevier/Butterworth-Heinemann, 2003.
Includes bibliographical references and index.
nmn 13/04/17
Loan
Keywords: Brand name products; Product management; Branding (Marketing)